Bolivia's New Constitution: Towards Participatory Democracy and Political Pluralism? - Almut Schilling-Vacaflor (German Institute of Global and Area Studies (GIGA), 2010)
In Bolivia, rights to increased political participation and the recognition of indigenous political systems are interrelated. The new constitution of 2009, a prime example of the 'new Andean constitutionalism', defines Bolivia as a representative, participatory and communitarian democracy. It incorporates enhanced mechanisms and institutions for participatory democracy. Moreover, new social rights have been anchored in the constitution and a plurinational state is supposed to be constructed. The article raises the question of whether the new constitution will change the relations between state and civil society considerably and whether a new democratic model is being established in Bolivia. I argue that there are many limiting factors when it comes to putting the emancipatory elements of the constitution into practice. These include the increased strength of the executive branch, the intent of the government to co-opt civil society organizations and to exclude dissident views, the resistance of the conservative opposition to loosing some of its privileges, the deep-rooted social inequality, the social conflicts and polarization, the resource dependence of the current economic model, and the authoritarian characteristics of indigenous self-governance structures. The article demonstrates that the new Bolivian constitution cannot create a new society but that the processes around the elaboration of a new basic law have contributed to considerable changes in the social, political and symbolic order. – – In Bolivien sind die Rechte für die vermehrte Beteiligung der Bevölkerung an politischen Entscheidungen mit der verstärkten Anerkennung von indigenen politischen Systemen verbunden. Die neue Verfassung, ein Paradebeispiel des 'neuen Anden-Konstitutionalismus', definiert Bolivien als repräsentative, partizipative und kommunitäre Demokratie. Zahlreiche neue Mechanismen und Institutionen einer partizipativen Demokratie waren im Grundgesetz von 2009 verankert worden. Mit der neuen Verfassung sollen Menschenrechte, darunter insbesondere soziale Rechte, gewährleistet und ein plurinationaler Staat geschaffen werden. Die Autorin untersucht, inwiefern die Rolle der Zivilgesellschaft im Staat durch die Verabschiedung einer neuen Verfassung verändert und welches Demokratiemodell im Rahmen der aktuellen Entwicklungen angestrebt wird. Richtet man den Blick auf die tatsächlichen Chancen, das neue Grundgesetz inklusive seiner emanzipatorischen Elemente anwenden zu können, treten maßgebliche einschränkende Faktoren deutlich hervor: Tendenzen der Machtkonzentration auf die Exekutive; Versuche der Regierungspartei, zivilgesellschaftliche Organisationen zu vereinnahmen und Dissidenten zu marginalisieren; der Widerstand der konservativen Opposition gegen den Verlust von Privilegien; Strukturen der sozialen Ungleichheit; soziale Konflikte und Polarisierung; die Ressourcenabhängigkeit des bolivianischen Entwicklungsmodells und autoritäre Charakteristika indigener Systeme der Selbstregierung. Die Hauptaussage des vorliegenden Artikels lautet, dass die neue Verfassung zwar per se keine neue Gesellschaft schaffen kann, jedoch die Abläufe rund um den verfassunggebenden Prozess einen Beitrag zur Veränderung der sozialen, politischen und symbolischen Ordnung Boliviens geleistet haben.
Keywords: 300; Bolivia; constitution; participatory democracy; indigenous peoples; social rights; political pluralism; Verfassungsreform; Partizipation; Indigene Völker; Pluralismus; Bolivien